2005
DOI: 10.1021/ja0441561
|View full text |Cite
|
Sign up to set email alerts
|

Binding and Condensation of Plasmid DNA onto Functionalized Carbon Nanotubes:  Toward the Construction of Nanotube-Based Gene Delivery Vectors

Abstract: Carbon nanotubes (CNTs) constitute a class of nanomaterials that possess characteristics suitable for a variety of possible applications. Their compatibility with aqueous environments has been made possible by the chemical functionalization of their surface, allowing for exploration of their interactions with biological components including mammalian cells. Functionalized CNTs (f-CNTs) are being intensively explored in advanced biotechnological applications ranging from molecular biosensors to cellular growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
464
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 733 publications
(477 citation statements)
references
References 52 publications
11
464
0
2
Order By: Relevance
“…[39][40][41][42][43] They are capable of crossing membranes to penetrate 80 into different types of cells without causing cell death, so both the cell functionality and the activity of the introduced molecules are preserved. [44][45][46] Based on this finding, CNTs have been successfully employed as nanovehicles for drug delivery [43,47,48] and for the transport of biomolecules, such as proteins, [49] peptides, [50] and DNA[42, 51,52], into cells. Additionally, based on their structural and chemical properties, CNTs can be envisioned as excellent carrier 85 candidates in immunization protocols.…”
Section: Introductionmentioning
confidence: 99%
“…[39][40][41][42][43] They are capable of crossing membranes to penetrate 80 into different types of cells without causing cell death, so both the cell functionality and the activity of the introduced molecules are preserved. [44][45][46] Based on this finding, CNTs have been successfully employed as nanovehicles for drug delivery [43,47,48] and for the transport of biomolecules, such as proteins, [49] peptides, [50] and DNA[42, 51,52], into cells. Additionally, based on their structural and chemical properties, CNTs can be envisioned as excellent carrier 85 candidates in immunization protocols.…”
Section: Introductionmentioning
confidence: 99%
“…CNTs have very recently been explored for the first time as novel materials for the complexation and delivery of gene-encoding nucleic acids [191,221]. However, the physicochemical interactions between CNTs and DNA have been studied under different contexts for much longer, particularly in attempts to disperse non-f -CNTs, and for the construction of sensors, nanocircuits, nanocomposites and gene delivery vectors.…”
Section: 71mentioning
confidence: 99%
“…An alternative functionalization reaction described by Georgakilas and coworkers produces positively charged ammonium-f -CNTs (CNT-NH 3 þ ) [146]. The interaction of CNT-NH 3 þ with plasmid DNA (pDNA) was studied in detail in our laboratories [221,233]. We have found that these f -CNTs interact with pDNA to form complexes primarily through electrostatic forces and that the pDNA was condensed around the CNT-NH 3 þ .…”
Section: 71mentioning
confidence: 99%
“…In this context, cationic and polycationic functionalised CNTs (f-CNTs) could represent a valuable alternative vector because of their capacity to easily enter into the cells to deliver plasmid DNA or short-interfering RNA. [39,40] Prato and co-workers have designed simple ammonium-f-CNTs and more sophisticated dendron-based nanotubes. [41][42] The different conjugates were used for gene-silencing experiments in vitro and in vivo demonstrating the capacity of such systems to deliver and eventually knock-down different genes efficiently.…”
Section: Introductionmentioning
confidence: 99%